2021
DOI: 10.1111/imm.13395
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic lymphoid follicles in progressive multiple sclerosis: From patients to animal models

Abstract: Ectopic lymphoid follicles (ELFs), resembling germinal centre‐like structures, emerge in a variety of infectious and autoimmune and neoplastic diseases. ELFs can be found in the meninges of around 40% of the investigated progressive multiple sclerosis (MS) post‐mortem brain tissues and are associated with the severity of cortical degeneration and clinical disease progression. Of predominant importance for progressive neuronal damage during the progressive MS phase appears to be meningeal inflammation, comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 126 publications
0
13
1
Order By: Relevance
“…Based on a previous report (Zrzavy et al, 2017), we performed double‐labeling experiments with anti‐podoplanin and anti‐FDC‐M1 antibodies, both markers for follicular dendritic cells (Köhler, 2010; Lohrberg & Wilting, 2016; Rodda et al, 2018; Schacht et al, 2005; Xie et al, 2008; Yu, Gibson, Pinkus, & Hornick, 2007). These follicular dendritic cells can also be found in certain CNS compartments ( i.e ., the subarachnoid space) under neuroinflammatory conditions (Ludewig et al, 2016; Zhan, Kipp, Han, & Kaddatz, 2021). As demonstrated in Figure 7, we found a clear co‐localization of both follicular dendritic cell markers with TMEM119, suggesting that TMEM119 is not specific for microglia but is also expressed by other cell types outside the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous report (Zrzavy et al, 2017), we performed double‐labeling experiments with anti‐podoplanin and anti‐FDC‐M1 antibodies, both markers for follicular dendritic cells (Köhler, 2010; Lohrberg & Wilting, 2016; Rodda et al, 2018; Schacht et al, 2005; Xie et al, 2008; Yu, Gibson, Pinkus, & Hornick, 2007). These follicular dendritic cells can also be found in certain CNS compartments ( i.e ., the subarachnoid space) under neuroinflammatory conditions (Ludewig et al, 2016; Zhan, Kipp, Han, & Kaddatz, 2021). As demonstrated in Figure 7, we found a clear co‐localization of both follicular dendritic cell markers with TMEM119, suggesting that TMEM119 is not specific for microglia but is also expressed by other cell types outside the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the original articles describing ELFs in patients with secondary progressive MS (SPMS) [ 55 ], the investigators found “a network of follicular dendritic cells producing CXCL13”. A recent review article on ELFs in MS [ 58 ] includes “presence of stromal/follicular dendritic cells expressing CXCL13” as one of the defining features of CNS ELFs in MS. However, ELFs have been generally only present in patients with progressive forms of MS, primarily those with SPMS.…”
Section: Two Logical Candidates For Molecular Biomarkers Based On The...mentioning
confidence: 99%
“…In addition, ectopic lymphoid follicles (ELFs), which resemble germinal center-like structures can be found in the meninges of 40% of the SPMS patients. ELFs were also observed in RRMS and PPMS patients but lack features of more developed follicles such as follicular dendritic cells (FDCs), and distinct T and B cell zones (22,23). ELFs can cause local antigen-specific responses within tissues and thereby support cortical degeneration and clinical disease progression (22).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…ELFs were also observed in RRMS and PPMS patients but lack features of more developed follicles such as follicular dendritic cells (FDCs), and distinct T and B cell zones (22,23). ELFs can cause local antigen-specific responses within tissues and thereby support cortical degeneration and clinical disease progression (22). Although the causes of MS are still unknown, next to a genetic predisposition, many different environmental factors such as vitamin D deficiency, obesity, smoking, and infection with the Epstein Barr virus (EBV) have been described to play a role in developing MS (2).…”
Section: Multiple Sclerosismentioning
confidence: 99%